Analysis of employee training needs in information technology industry. (2015) - Agarwal, Neetima; Pande, Neerja; Ahuja, Vandana
Information technology industry is the fastest booming and high-gross profit making industry in the world. The employability size of this industry is no wonder very high and covers a major proportion of the service sector. This industry is the perfect model of individual skills, team-cohesion and organisational success hence it is a complete role-model industry to visualise both people-oriented and work-oriented approach at the same time. This paper will put forward all essential skills like communication, team-work, critical thinking, etc. needed most at the time of employability and will try to find the way to make the training of these soft skills more effective. The data has been collected from few IT companies by interviewing different sets of people working at different levels. It is of high importance to every person in this industry to acquire adequate soft skills as it's the parameter to judge the whole personality.